Cacing Tanah (Lumbricus Rubellus) Sebagai Agen Bioremediasi Tanah Tercemar Minyak Bumi dengan Penambahan Vermikompos Sebagai Bulking Agent - Reynaldi Saputra; Lita Darmayanti; Muhardi Muhardi (Jurnal Daur Lingkungan, 2022)
Petroleum is one of natural resources. Provinsi Riau is one of the petroleum producers in Indonesia. Exploitationsuch as petroleum drilling can result in pollution on the lands in the area around drilling. One method of processing contaminated oil waste that is relatively economical, easy and environmentally friendly is bioremediation. This research aims to process oil-polluted soil with bioremediationusing vermikomposting techniques. The study was conducted by varying the ratio of the weight of polluted soil with vermikompos, 1:2; 1:1; 2:1 (b/b). Observations were made over 49 days. During the study pH values, temperature, and water content were observed. The results showed the best results in reactors with a ratio ofpolluted soil and vermikompos (1:2) w/w, with an additional 20 worms with an allowance efficiency of 85.19%. pH values during observation ranged from 7-8, temperatures were 25ºC, and water levels fluctuated from 81-141%. The addition of 5% of rice husks to reactors with polluted soil composition: vermikompos (1:2) can increase the efficiency of the allowance to 90.05%.